2019
DOI: 10.3390/ijms21010076
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-204 Deficiency in Human Aortic Valves Elevates Valvular Osteogenic Activity

Abstract: Aortic valve interstitial cells (AVICs) play a major role in valvular calcification associated with calcific aortic valve disease (CAVD). Although AVICs from diseased valves display a pro-osteogenic phenotype, the underlying mechanism causing this remains unclear. MicroRNA-204 (miR-204) is a negative regulator of osteoblast differentiation. We sought to analyze miR-204 expression in diseased human aortic valves and determine the role of this miR in AVIC osteogenic activity associated with CAVD pathobiology. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…It also showed the ability to target CXCL12, coding for SDF-1α, an angiogenic factor and, notably, the silencing of miR-137-3p could favor both osteogenesis and angiogenesis [ 181 ]. MiR-204 deficiency has been found to be involved in the increased osteogenic activity associated with calcific aortic valve disease [ 182 ]. This result agrees with several studies reporting that in different mesenchymal progenitor cell lines, such as C3H10T1/2, C2C12, ST2 and primary BM-MSCs, miR-204, targeting RUNX2, negatively controls osteogenic differentiation [ 94 , 183 ].…”
Section: Osteogenic Differentiation By Mirna Regulationmentioning
confidence: 99%
“…It also showed the ability to target CXCL12, coding for SDF-1α, an angiogenic factor and, notably, the silencing of miR-137-3p could favor both osteogenesis and angiogenesis [ 181 ]. MiR-204 deficiency has been found to be involved in the increased osteogenic activity associated with calcific aortic valve disease [ 182 ]. This result agrees with several studies reporting that in different mesenchymal progenitor cell lines, such as C3H10T1/2, C2C12, ST2 and primary BM-MSCs, miR-204, targeting RUNX2, negatively controls osteogenic differentiation [ 94 , 183 ].…”
Section: Osteogenic Differentiation By Mirna Regulationmentioning
confidence: 99%
“…Furthermore, miR-125b was found to be downregulated in an in vivo model of atherosclerosis and aortic calcification in mice (Goettsch et al, 2011;Rangrez et al, 2012;Coffey and Jones, 2014), while miR-223 was overexpressed in calcified murine aortas (Rangrez et al, 2012). Human calcific aortic valve disease is associated with significantly reduced miR-204 levels and miR-204 mimics suppressed the osteogenic activity of interstitial cells from diseased valves (Song et al, 2020).…”
Section: Osteogenic Milieumentioning
confidence: 99%
“…Because the expression level of hsa-miR-374c-3p in valves was lower than the other five miRNAs, we removed it from the candidate miRNAs. Among the five candidate miRNAs, it was previously reported that the expression of miR-204-5p was decreased in calcified aortic valves and inhibited the osteogenic differentiation of VICs and aortic valve calcification (Yu et al, 2018;Song et al, 2019). Then, we calculated the correlation of five candidate miRNAs with the osteogenic genes RUNX2.…”
Section: The Verification Of Downregulated Candidate Mirnas In Calcified Aortic Valvesmentioning
confidence: 99%
“…Compared with normal human aortic valves, the miRNA expression profiles in calcified aortic valve tissues have changed (Wang et al, 2017). Several miRNAs [miR-204-5p (Yu et al, 2018;Song et al, 2019), miR-143 (Fiedler et al, 2019), miR-125b (Ohukainen et al, 2015), miR-34a (Toshima et al, 2020), etc. ] have been reported to participate in the osteogenic differentiation of VICs and valve calcification.…”
Section: Introductionmentioning
confidence: 99%